An Application of Electronic Certificate Policy Innovation (E-Suket) in Rejomulyo Village and Balowerti Village, Kediri City - Idat, Iradhad Taqwa; Habib Abdul Aziz; Romadhan, Achmad Apriyanto; Kamil, Muhammad (Universitas Muhammadiyah Surakarta, 2022)
The Department of Communication and Information of Kediri City made an innovative service, namely the Electronic Certificate (E-Suket) to facilitate the administration of making letters in the village government, which was manual system but now electronic-based. It is hoped that this innovation can help the community to create effective and efficient administrative services. The purpose of this study was to determine the application of E-Suket services in Rejomulyo and Balowerti Villages. The research method used is descriptive qualitative to provide an explanation of the Application of Electronic Policy Certificate (E-Suket) as a public service effort in the City of Kediri. Data collection techniques used are observation, interviews, and documentation. The concept used to analyze is Edwards III regarding Policy Implementation which focuses on communication, resources, disposition, and bureaucratic structure. The results of this study indicate that the implementation of E-Suket services as a whole has been going well. However, there are problems in the implementation process, such as in the bureaucratic structure, there is no Standard Operating Procedure (SOP) in the implementation of this E-Suket. The Communications and Informatics Service needs to immediately make SOPs for E-Suket services in order to create clear standardization in the service process.